Enhancing Education in Elementary Schools through Gamified Learning: Exploring the Impact of Kahoot! on the Learning Process - Baraa Rayan; Abeer Watted (MDPI AG, 2024)
The integration of technology in educational settings has gained popularity, aiming to enhance student engagement and motivation. Kahoot! digital tool activities have emerged as a favored choice for creating dynamic and captivating learning environments. This study investigates the impact of incorporating Kahoot! on students' learning outcomes and motivation to learn science. The research utilized a quantitative methodology, collecting data through pre- and post-questionnaires administered to both experimental (N = 53) and control groups (N = 56). This study identified that integrating Kahoot! activities led to a significant improvement in students' grasp of scientific concepts and principles. Moreover, a noteworthy increase in self-efficacy, interest, and enjoyment levels was observed among students in the experimental groups. This indicates that Kahoot! activities not only enhance students' understanding of scientific concepts but also amplify their motivation to engage with the subject matter. This study also explored potential demographic variables that could influence these outcomes. Notably, the findings suggest that grade level plays a role in students' motivation to learn science. In conclusion, this study underscores the potential of Kahoot! activities to positively influence students' science learning experiences, emphasizing the importance of cultivating dynamic and captivating learning environments.